LEARN A LANGUAGE, EMBRACE A CULTURE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 The recently concluded 6 International Language Learning Conference (ILLC) 2015, organised by the School of Languages, Literacies and Translation (PPBLT) USM, ended with a lively note, after numerous sessions of exchanging notes and opinions.